Corporate video of Open University Malaysia - University for All - CiDT , Centre for Instructional Design & Technology (2010)
In Malaysia, the provision for education is the biggest challenge for the government as the nation strives to become a fully developed country by the year 2020. One solution is to use technology as an enabler to bring education to the masses. Universities are taking up the challenge by updating the content of their programmes but more importantly, utilising the latest technologies to improve the delivery systems. One of the emerging delivery systems much talked about is Open and Distance Education which is fast becoming the way of providing education to the masses.